2017
DOI: 10.1111/bph.13943
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the plasma membrane in metabolic disease: impact of the membrane environment on G protein‐coupled receptor structure and function

Abstract: This article is part of a themed section on Molecular Pharmacology of GPCRs. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v175.21/issuetoc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 192 publications
(268 reference statements)
0
38
0
Order By: Relevance
“…G q/11 protein signalling regulates the activity of numerous cytosolic and transmembrane proteins. CCK 1 receptors, similar to K V 7.2/K V 7.3 channels and GABA A receptors, previously referred to, exhibit a particular sensitivity to plasma membrane cholesterol content, where both depletion and increase of cholesterol inhibit their activity (Desai et al, 2016; Desai & Miller, 2018; Potter, Harikumar, Wu, & Miller, 2012; Harikumar et al, 2005). Harikumar et al (2005) and Potter et al (2012) showed that cholesterol depletion significantly decreased the agonist binding affinity to CCK 1 receptors, while enrichment of plasma membrane cholesterol content actually increased CCK 1 binding affinity.…”
Section: Gpcr Cck1 Signalling Is Biphasic‐dependent Of Plasma Membranmentioning
confidence: 99%
See 2 more Smart Citations
“…G q/11 protein signalling regulates the activity of numerous cytosolic and transmembrane proteins. CCK 1 receptors, similar to K V 7.2/K V 7.3 channels and GABA A receptors, previously referred to, exhibit a particular sensitivity to plasma membrane cholesterol content, where both depletion and increase of cholesterol inhibit their activity (Desai et al, 2016; Desai & Miller, 2018; Potter, Harikumar, Wu, & Miller, 2012; Harikumar et al, 2005). Harikumar et al (2005) and Potter et al (2012) showed that cholesterol depletion significantly decreased the agonist binding affinity to CCK 1 receptors, while enrichment of plasma membrane cholesterol content actually increased CCK 1 binding affinity.…”
Section: Gpcr Cck1 Signalling Is Biphasic‐dependent Of Plasma Membranmentioning
confidence: 99%
“…For example, both plasma membrane trafficking (Kitson, Mullen, Cogdell, Bill, & Fraser, 2011; Kumar & Chattopadhyay, 2020) and functioning of the GPCR depend on the membrane cholesterol content (Chini & Parenti, 2004; Licon et al, 2015; Gimpl, 2016; Desai & Miller, 2018). This regulatory action on proteins is associated with either cholesterol effects on the biophysical properties of the plasma membrane or direct interaction of GPCR–cholesterol (Cherezov et al, 2007; Wu et al, 2014; Rouviere, Arnarez, Yang, & Lyman, 2017; Desai & Miller, 2018). The cholecystokinin‐1 (CCK 1 ) receptor belongs to Class A GPCR and regulates diverse physiological processes as gallbladder contraction, pancreatic secretion, gastroenteric motility and appetite (Gibbs, Young, & Smith, 1973; Chandra & Liddle, 2007).…”
Section: Gpcr Cck1 Signalling Is Biphasic‐dependent Of Plasma Membranmentioning
confidence: 99%
See 1 more Smart Citation
“…GPCRs are amongst the most commonly examined targets for drug development. As outlined in the article by Desai and Miller (), the early stages of drug development often involve the use of recombinant systems that may assume that the cellular environment of the receptor has little influence on the cellular response. While much work has studied the influence of agonists, antagonists, G proteins and other receptors present in the plasma membrane on receptor conformation, it is now becoming increasingly clear that other membrane proteins and lipids also influence receptor function (Prieto et al ., ).…”
mentioning
confidence: 99%
“…In addition, it is clear that lipid rafts rich in these components form membrane microdomains that concentrate signalling and regulatory proteins (Pike, ; Ray et al ., ). There are now many examples demonstrating the influence of cholesterol on GPCR function and regulation (see Desai and Miller, ). The lipid composition of the cell membrane also influences the distribution and function of the primary GPCR effectors, G proteins.…”
mentioning
confidence: 99%